Perancangan Batik di Sekolah Menengah Kejuruan - Sari Yuningsih (JURNAL RUPA, 2018)
Batik has been known as a cultural heritage as an oral and non-artistic culture typical of Indonesia. The recognition of batik as one of the cultural heritage faces a challenge that is how the effort of preservation and regeneration of batik in the future. Batik preservation is not just applying batik in daily activities, but it needs conservation in the context of science and skills. In order to preserve Vocational High School (SMK) is the right tool in regenerating batik as insight, knowledge and skill. For that need special attention to continue to foster vocational school in order to continue to exist in the competition. This study contains descriptive description of vocational school of textile craft that holds batik subjects as a form of batik preservation in the world of formal education. Writing method in this study using literature study, observation, interview and documentation at one school in Bandung. With this exposure is expected to provide an overview of the implementation of batik subjects and can be used as a reference in the study of batik development in vocational school.